Penggambaran Intervensi Militer ECOWAS di Gambia: Analisis isi dari point news media - Jawla, Famara Wassa; Maksum, Ali; Bustami, Reevany (The Journal of Society and Media, 2024)
This study examines how the Point News Media portrayed the ECOWAS military intervention in The Gambia. ECOWAS intervened when former President Yahya Jammeh refused to step down after losing the 2016 election. Scholars and the media worldwide discussed the intervention's legality and legitimacy in promoting the democratic transfer of power in the region. Initially, the intervention was praised for successfully promoting democratic change in a region that is prone to coups. However, the public later requested the withdrawal of the intervention force. The study analyzed 64 news articles published between 2017 and 2023. Ten frames were identified: dissatisfaction, ECOMIG mandate, ECOMIG success, instability, legitimacy, reassurance, social service, support, uncertainty, and confrontation. The Point news media portrayed the intervention negatively, characterized by dissatisfaction and confrontation in implementing the intervention's mandate. This negative depiction may have contributed to the shift in public discourse towards requesting the ECOWAS military withdrawal. The study used qualitative content analysis as a data gathering and analysis method to explore the portrayal of the intervention. This method allowed the researchers to identify the different frames used to depict the intervention. By presenting the findings in simple language, the study increases accessibility and understanding of the topic.